Current status of bariatric surgery - Young Suk Park (Society of Gastrointestinal Intervention, 2022)
The prevalence of obesity has increased steadily both in Korea and throughout the world, and bariatric surgery is the most powerful treatment modality for morbid obesity. Robotic digital platforms provide potential benefits such as three-dimensional visualization, wristed instruments that lead to enhanced dexterity, and blocked torque transmission to ports. These advantages are remarkable when robotic systems are employed for bariatric surgery. If robotic bariatric surgery can be demonstrated to be clinically safer than other approaches, it could become the standard procedure.